2014
DOI: 10.12659/ajcr.889961
|View full text |Cite
|
Sign up to set email alerts
|

Successful anesthesia and hip surgery in a 107-year-old patient

Abstract: Patient: Female, 107Final Diagnosis: Hip fractureSymptoms: —Medication: —Clinical Procedure: Hip surgerySpecialty: Orthopedics and TraumatologyObjective:Rare diseaseBackground:In modern societies, elderly populations have increased over the last four decades and have become the main clients of medical services. A hip fracture is a significant injury for anyone, but for older people it can be catastrophic.Case Report:A 107-year-old female was admitted with fracture of the right hip. The patient took a single 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…[ 3 4 ] We have reported a reduced length of stay, number of suspension, the duration of fasting, the release the feedback, the length of stay in the postanesthetic care unit (PACU), and incidence of hypotension in elderly patients undergoing chip surgery and who received fast-track perioperative care. [ 5 6 7 8 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 4 ] We have reported a reduced length of stay, number of suspension, the duration of fasting, the release the feedback, the length of stay in the postanesthetic care unit (PACU), and incidence of hypotension in elderly patients undergoing chip surgery and who received fast-track perioperative care. [ 5 6 7 8 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…The medical evaluation for patients with advanced ages should focus on identifying risk factors, optimizing status, predicting complications, and providing appropriate information. Some studies have described cases of surgery in patients aged >100 years, for example, coronary bypass surgery in a 105-year-old patient 3) , abdominal wall reconstruction in a 105-year-old patient 4) , and osteosynthesis for hip fracture in a 107-year-old patient 5) . They reported that in each case, detailed risk assessment, surgical planning, and meticulous postoperative management were the reasons for the successful surgical treatment [3][4][5] .…”
Section: Discussionmentioning
confidence: 99%
“…The blood loss in PSA is comparable to that of other approaches [ 16 ]. It is acknowledged that the blood loss is more dependent on patient factors such as the severity of the acetabular fracture, associated injuries, coagulability, and bone bleeding [ 6 , 8 , 16 , 23 ], and it does not affect the outcome score [ 6 ]. In a hip fracture, the blood loss could exceed one liter.…”
Section: Discussionmentioning
confidence: 99%
“…In a hip fracture, the blood loss could exceed one liter. In such cases, a less invasive incision is preferred [ 23 ]. Moreover, prolonged traumatic surgical dissection is known to increase the incidence of heterotopic ossification [ 8 ].…”
Section: Discussionmentioning
confidence: 99%